Biomarker Baru Monoclonal Antibody Fragmentasi Collagen Type IV Untuk Mendeteksi Acute Myocard Infarction Terkait Infeksi Perviromonas Gingivalis - Ketut Muliartha; Mulyohadi Ali; Djanggan Sargowo (The Indonesian Heart Association, 2011)
Background. Index mortality of atherosclerotic very high. The research conducted by WHO in 1995 show 20% of IMA mortality caused by ath-erosclerotic. The new emerging risk factor infection is the Perviromonas gingivalis. The objective of study to detect IMA in blood sample by using biomarker monoclonal antibody collagen type IV.Method. This research was experimental in vitro with ethic clearance and carried on the biomedic Laboratory, Brawijaya University. The subject were (n=12) and healthy people are (n=4). To show expression of MMP-9 and fragmentation of collagen type IV use western blotting tecnique. The monoclonal antibody were obtain which sub cutan imunization followed by isolating lymphocytes and fusing with myeloma cell to growth of hibridoma and produce antibody. Result. Found in following MMP-9 product the band were 92 kDa and the collagen type IV fragmentation band 60-90 kDa. To test for biomarker reac-tion monoclonal antibody fragmentation collagen type IV in blood sample 1-12 was positive for AMI.Conclusion. The biomarker for monoclonal antibody fragmentation col-lagen type IV shown AMI reaction positive.